New Frontiers in Diagnosing and Combating Corruption - Kaufmann, Daniel; Pradhan, Sanjay; Ryterman, Randi (World Bank, Washington, DC, 2012)
The World Bank has helped Albania, Georgia, and Latvia measure corruption and design strategies to combat it and improve governance. This note explains how empirical surveys can inform and transform the policy dialogue, so that a workable anticorruption agenda can be established. Early results are given as well as emerging conclusions. Also, challenges in performing these surveys are highlighted, as well as in translating survey results into institutional reform priorities.